The Influence of Brand Equity, Price and Service Quality on Vapor Product Purchase Decisions: Pengaruh Ekuitas Merek, Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian Produk Vapor - Prayogo, Kurniawan Didit; Sari, Herlinda Maya Kumala (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine, explain and analyze the effect of Brand Equity, Price, and Service Quality on Vapor Product Purchase Decisions on Vapeboss Sidoarjo. This research is based on a fact in the company that if the brand equity in Vapeboss Sidoarjo is high, it will add value to consumers, as well as the price at Vapeboss Sidoarjo which is affordable so that it can compete with other stores. However, this is also balanced with the quality of service at the Vapeboss Sidoarjo store so that consumers continue to survive and use products at Vapeboss Sidoarjo. This study uses quantitative methods, data collection techniques using questionnaires, distributed to 100 respondents who have used Vapeboss Sidoarjo products. The data analysis technique used in this study is multiple linear regression using SPSS (Statistical Program for Social Science) version 25. The results of this study prove that brand equity variables affect consumer decisions, price variables affect consumer decisions, service quality affects on consumer decisions, and brand equity, price and service quality variables have a simultaneous effect on purchasing decisions for vapor products at Vapeboss Sidoarjo.